P9 Low false positive rate of gonorrhoea cases referred to gum from a low prevalence chlamydia screening population. (18th May 2015) - Tan, Agnieszka; Brolly, Stephen; Howard, Neil; Dervisevic, Samir; Evans, Jo
Abstract : Background/introduction: Recent national guidance for the detection of gonorrhoea (GC) has raised concerns that the majority of initial positive GC test results are likely to be false positives when a low prevalence population is screened using a nucleic acid amplification test (NAAT). Our local chlamydia screening programme uses a dual NAAT for chlamydia and GC and has a low reactive GC rate <1%. All GC reactive cases are referred to GUM for further investigation. Aim(s)/objectives: To determine whether GC reactive cases referred from our local chlamydia screening programme were true GC infections or likely to be false positive cases. Methods: A retrospective case notes review of 13 consecutive GC reactive cases seen at our clinic referred from the local chlamydia screening programme. Results: 10/13 were women. 10/13 cases were confirmed as true GC infections by positive genital GC cultures. In 1 case genital culture was negative but screening and supplementary NAAT with a different target confirmed a true GC infection. In 1 case genital cultures were negative however pharyngeal culture was positive indicating a true GC infection. In 1 case GC cultures were all negative but NAAT tests were reactive from genital and pharyngeal sites and equivocal from the rectum. Discussion/conclusion: Only 1/13 GC reactive cases seen in our GU referred from a low prevalence screening population might have been a false positive. Contrary to recent publications, in our area, using a dual NAAT is unlikely to lead to high numbers of false positive GC results.